Integrasi Kurikulum Berbasis Cinta dalam Materi PAI: Strategi Internalisasi Kasih Sayang dan Toleransi di Madrasah - Windayani Nurmatias; Deby Kartika; Sri Dwy Rahayu; Nadia Fajira (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
Religious education in plural societies requires a pedagogical approach that connects doctrinal understanding with compassion, tolerance, social responsibility, and peaceful coexistence. This study aimed to synthesize the integration of Indonesia’s Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) into Islamic Religious Education (Pendidikan Agama Islam/PAI) in madrasahs and to formulate an operational framework for internalizing compassion and tolerance. A systematic literature review was conducted following PRISMA 2020 by searching the Scite scholarly index and conducting supplementary citation tracking for publications issued between 2024 and 31 December 2025. Of 87 records identified, 20 articles met the eligibility criteria, while the official 2025 KBC guideline was analyzed separately as the primary policy document. Data were extracted using a structured matrix and synthesized through deductive and inductive thematic analysis, with evidence classified as empirical, document-analytical, or conceptual. The findings indicate that KBC is organized around five official themes: love for Allah and His Messenger, knowledge, the environment, oneself and others, and the homeland, while compassion and tolerance function as cross-cutting values. Effective integration depends on the alignment of learning outcomes, contextualized PAI content, teacher modelling, dialogical-reflective activities, authentic social and environmental projects, supportive madrasah culture, and evidence-based affective assessment. However, the existing evidence remains dominated by qualitative, conceptual, and single-site studies, limiting causal and longitudinal conclusions. This study contributes an evidence-informed matrix linking the five themes to PAI content, pedagogical strategies, observable indicators, and implementation conditions; practically, the findings imply that madrasahs should strengthen teacher training, instructional supervision, school culture, and validated affective assessment to ensure that KBC is implemented substantively rather than administratively.